Effectiveness and cost-effectiveness for the treatment of depressive symptoms in refugees and asylum seekers: a multi-centred randomized controlled trial - Böge, Kerem; Karnouk, Carine; Hoell, Andreas; Tschorn, Mira; Kamp-Becker, Inge; Padberg, Frank; Übleis, Aline; Hasan, Alkomiet; Falkai, Peter; Salize, Hans Joachim; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; et al. (The lancet. Regional health, 2022)
Background - Current evidence points towards a high prevalence of psychological distress in refugee populations, contrasting with a scarcity of resources and amplified by linguistic, institutional, financial, and cultural barriers. The objective of the study is to investigate the overall effectiveness and cost-effectiveness of a Stepped Care and Collaborative Model (SCCM) at reducing depressive symptoms in refugees, compared with the overall routine care practices within Germany's mental healthcare system (treatment-as-usual, TAU). - Methods - A multicentre, clinician-blinded, randomised, controlled trial was conducted across seven university sites in Germany. Asylum seekers and refugees with relevant depressive symptoms with a Patient Health Questionnaires score of ≥ 5 and a Refugee Health Screener score of ≥ 12. Participants were randomly allocated to one of two treatment arms (SCCM or TAU) for an intervention period of three months between April 2018 and March 2020. In the SCCM, participants were allocated to interventions tailored to their symptom severity, including watchful waiting, peer-to-peer- or smartphone intervention, psychological group therapies or mental health expert treatment. The primary endpoint was defined as the change in depressive symptoms (Patient Health Questionnaire-9, PHQ-9) after 12 weeks. The secondary outcome was the change in Montgomery Åsberg Depression Rating Scale (MADRS) from baseline to post-intervention. - Findings - The intention-to-treat sample included 584 participants who were randomized to the SCCM (n= 294) or TAU (n=290). Using a mixed-effects general linear model with time, and the interaction of time by randomisation group as fixed effects and study site as random effect, we found significant effects for time (p < .001) and time by group interaction (p < .05) for intention-to-treat and per-protocol analysis. Estimated marginal means of the PHQ-9 scores after 12 weeks were significantly lower in SCCM than in TAU (for intention-to-treat: PHQ-9 mean difference at T1 1.30, 95% CI 1.12 to 1.48, p < .001; Cohen's d=.23; baseline-adjusted PHQ-9 mean difference at T1 0.57, 95% CI 0.40 to 0.74, p < .001). Cost-effectiveness and net monetary benefit analyses provided evidence of cost-effectiveness for the primary outcome and quality-adjusted life years. Robustness of results were confirmed by sensitivity analyses. - Interpretation - The SSCM resulted in a more effective and cost-effective reduction of depressive symptoms compared with TAU. Findings suggest a suitable model to provide mental health services in circumstances where resources are limited, particularly in the context of forced migration and pandemics. - Funding - This project is funded by the Innovationsfond and German Ministry of Health [grant number 01VSF16061]. The present trial is registered under Clinical-Trials.gov under the registration number: NCT03109028. https://clinicaltrials.gov/ct2/show/NCT03109028
Online verfügbar: 6. Juni 2022, Artikelversion: 6. Juni 2022
Gesehen am 26.08.2024